Organizational Citizenship Behaviour dan Motivasi Kerja Terhadap Kinerja - Tiara Namora Tarigan (IPM2KPE, 2023)
The purpose of this study was to determine the effect of organizational citizenship behavior and work motivation on the performance of health workers mediated by burnout at Seto Hasbadi Hospital, Bekasi. The research method used in this research is descriptive with a quantitative approach. The population is 150 people. The sampling technique used total sampling so that the number of samples in this study was 150 respondents. Data analysis technique using path analysis. The results of the study show, a) there is a positive and significant effect of organizational citizenship behavior on performance with tcount > ttable, namely 17,168 > 1,976 and a probability value of 0,000, which is below 0,005; b) there is a positive and significant effect of work motivation on performance with tcount > ttable, namely 9,491 > 1,976 and a probability value of 0,000, which is below 0,005; c) there is a positive and significant effect of burnout on performance with tcount > ttable, namely 10,884 > 1,976 and a probability value of 0,000, which is below 0,005. The conclusions in this study are, a) Organizational Citizenship Behavior has a positive and significant effect on performance; b) Work Motivation has a positive and significant effect on performance; c) Burnout has a positive and significant effect on performance; d) the direct effect of Organizational Citizenship Behavior on performance has a greater value than the indirect effect of Organizational Citizenship Behavior on performance through burnout; e) The indirect effect of work motivation on performance through burnout has a greater value than the direct effect of work motivation on performance. Keywords: Burnout, Performance, Work Motivation, Organizational Citizenship Behavior